Diplomasi Digital Tiongkok dan Digital Silk Road: Implikasi Bagi Negara-Negara Global South - Novi Amalia; Sartika Soesilowati; Siti Rochmawati Soesanto (Parahyangan Center for International Studies, 2026)
Digital transformation in contemporary international politics has catalyzed fundamental shifts in diplomatic mechanisms and the power projection of major powers, with China strategically leveraging digital infrastructure through the Digital Silk Road as a geopolitical instrument. This research comprehensively analyzes the characteristics of China’s digital diplomacy through the Digital Silk Road and examines its multidimensional implications for digital sovereignty, cybersecurity, economic development, and socio-political dynamics in Global South countries. This study employs a qualitative library research approach using narrative literature review methodology, analyzing academic publications from Scopus, Google Scholar, and Web of Science databases spanning 2021-2025 through systematic qualitative content analysis. Findings reveal that the Digital Silk Road creates complex dilemmas for Global South nations between accelerating digital transformation and risks to digital sovereignty, alongside potential transfer of digital authoritarianism models. Heterogeneity in recipient countries’ responses reflects variations in state capacity, domestic political structures, and positions within the global digital economy. This expansion contributes significantly to internet fragmentation into distinct geopolitical spheres of influence, accelerating competition among digital sovereignty models promoted by China, the United States, and the European Union in their contest for influence across the Global South. Keywords: digital authoritarianism, digital diplomacy, Digital Silk Road, digital sovereignty, Global South